For the Greater Good: Protection of Psychological Test Material. Issue 6 (1st November 2016) - Mathews, R.; Pratt, C.
Abstract : A key aspect of psychological work is formal psychological testing using standardised tests and procedures. In Australia formal psychological testing is unique to psychologists and psychologists' training and ethical obligations under their Code of Ethics requires that they seek to protect test material from scrutiny by non-psychologists. Legal requests for psychological test material leading to exposure of such material is not in the public interest as it can lead to misuse, misinterpretation, and damage to the integrity of the test for future use by the public through the loss of effective assessment tools. This effectively results in harm to the public. This article aims to increase understanding of the reasons that psychologists seek to restrict access to formal psychological test material, identifies legal precedents to support the protection of the material, and provides a process for relevant outcomes of psychological testing to be used for legal purposes.